IPTEKS PERAN BI TERHADAP TRANSFER DANA MELALUI SISTEM KLIRING NASIONAL PT. BANK SULUTGO - Chandra, Cherry Agustine; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
Along with the development of the times, information technology is very helpful in conducting transactions using BI-RTGS. The need for clearing is increasing. The clearing operation carried out by Bank Indonesia makes it easy to calculate interbank debt and save energy, time and costs. The purpose of clearing is to advance and facilitate payment of demand deposits, with easy, safe and efficient implementation, it is necessary to understand how the calculation of interbank notes, calculation of scripts in the clearing area.Keywords: Kliring, BI, Warkat